2010
DOI: 10.1017/s0031182010000120
|View full text |Cite
|
Sign up to set email alerts
|

Inventory and analysis of ATP-binding cassette (ABC) systems inBrugia malayi

Abstract: ABC systems are one of the largest described protein superfamilies. These systems have a domain organization that may contain 1 or more transmembrane domains (ABC_TM1F) and 1 or 2 ATP-binding domains (ABC_2). The functions (e.g., import, export and DNA repair) of these proteins distinguish the 3 classes of ABC systems. Mining and PCR-based cloning were used to identify 33 putative ABC systems from the Brugia malayi genome. There were 31 class 2 genes, commonly called ABC transporters, and 2 class 3 genes. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…Multiple ABC transporter genes have been reported in free-living and parasitic nematodes (Sheps et al, 2004;Ardelli et al, 2010;Laing et al, 2013). The overexpression of some of these transporters has been observed in drug-resistant isolates of different nematode species compared to susceptible reference isolates (Dicker et al, 2011;Williamson et al, 2011;Sarai et al, 2013;Raza et al, 2016), suggesting a potential role for ABC transporters in anthelmintic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple ABC transporter genes have been reported in free-living and parasitic nematodes (Sheps et al, 2004;Ardelli et al, 2010;Laing et al, 2013). The overexpression of some of these transporters has been observed in drug-resistant isolates of different nematode species compared to susceptible reference isolates (Dicker et al, 2011;Williamson et al, 2011;Sarai et al, 2013;Raza et al, 2016), suggesting a potential role for ABC transporters in anthelmintic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…There have been various reports describing the presence of genes that encode different ABC transporters in nematodes including H. contortus (Laing et al, 2013), C. elegans , Brugia malayi (Ardelli et al, 2010), Te. circumcincta (Dicker et al, 2011) and O. volvulus (Huang and Prichard, 1999).…”
Section: Methods Of Studying Abc Transportersmentioning
confidence: 99%
“…C. elegans is known to have 15 P-gp genes (pgp), eight MRP (mrp) and nine HAF genes (haf) . In parasitic nematodes, eight P-gp, five MRPs and eight HAF transporter genes were reported in Brugia malayi (Ardelli et al, 2010), two P-gp genes in cyathostomins (Drogemuller et al, 2004), 11 partial sequences of P-gp genes in Te. circumcincta (Dicker et al, 2011) and four P-gp and three HAF encoding genes have been reported in Onchocerca volvulus (Huang and Prichard, 1999;Bourguinat et al, 2008).…”
Section: Abc Transporters In Nematodesmentioning
confidence: 99%
See 2 more Smart Citations